2015
DOI: 10.1209/0295-5075/109/24001
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of a dilute suspension of self-propelled particles

Abstract: With a detail microscopic model for a self-propelled swimmer, we derive the rheological properties of a dilute suspension of such particles at small Peclet numbers. It is shown that, in addition to the Einstein's like contribution to the effective viscosity, that is proportional to the volume fraction of the swimmers, a contribution due to the activity of self-propelled particles influences the viscosity. As a result of the activity of swimmers, the effective viscosity would be lower (higher) than the viscosit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These includes a class of phenomena ranging from coherent motion of two coupled swimmers [39][40][41] to pattern formation and reduction of effective viscosity in suspensions. [42][43][44][45][46] Inspiring from these hydrodynamical systems, we expect to see a rich physical behavior in the case of Janus particles those are electro-hydrodynamical and in addition to hydrodynamic effects, the presence of long range electrostatic forces should also be considered.…”
Section: -35mentioning
confidence: 99%
“…These includes a class of phenomena ranging from coherent motion of two coupled swimmers [39][40][41] to pattern formation and reduction of effective viscosity in suspensions. [42][43][44][45][46] Inspiring from these hydrodynamical systems, we expect to see a rich physical behavior in the case of Janus particles those are electro-hydrodynamical and in addition to hydrodynamic effects, the presence of long range electrostatic forces should also be considered.…”
Section: -35mentioning
confidence: 99%
“…Experimental [30][31][32][33] and particle-based computational realizations [10,[34][35][36][37][38] in the stable regime clearly demonstrate nontrivial flow and enhanced mixing even though the activity is less organized and vigorous than in unstable pusher systems. Such nontrivial dynamics can only be described by including the finite particulate nature of the microswimmers.…”
Section: Introductionmentioning
confidence: 99%
“…Later theory by Giomi et al revealed even richer dynamics and predicted the existence of shear banding, yield stress, and "superfluidity" of active fluids (22). Unusual rheology of active fluids has also been studied based on the microhydrodynamics of microswimmers at low concentrations (23)(24)(25)(26)(27), swimming pressures (28) and gener-alized Navier-Stokes equations (29). Experimentally, Sokolov et al and Gachelin et al showed the low viscosity of bacterial suspensions in thin films (30,31).…”
mentioning
confidence: 99%